Evolution of phenotypic plasticity: Genetic differentiation and additive genetic variation for induced plant defence in wild arugula Eruca sativa. (24th November 2019) - Ogran, Ariel; Conner, Jeffrey; Agrawal, Anurag A.; Barazani, Oz
Abstract: Phenotypic plasticity is the primary mechanism of organismal resilience to abiotic and biotic stress, and genetic differentiation in plasticity can evolve if stresses differ among populations. Inducible defence is a common form of adaptive phenotypic plasticity, and long‐standing theory predicts that its evolution is shaped by costs of the defensive traits, costs of plasticity and a trade‐off in allocation to constitutive versus induced traits. We used a common garden to study the evolution of defence in two native populations of wild arugula Eruca sativa (Brassicaceae) from contrasting desert and Mediterranean habitats that differ in attack by caterpillars and aphids. We report genetic differentiation and additive genetic variance for phenology, growth and three defensive traits (toxic glucosinolates, anti‐nutritive protease inhibitors and physical trichome barriers) as well their inducibility in response to the plant hormone jasmonic acid. The two populations were strongly differentiated for plasticity in nearly all traits. There was little evidence for costs of defence or plasticity, but constitutive and induced traits showed a consistent additive genetic trade‐off within each population for the three defensive traits. We conclude that these populations have evolutionarily diverged in inducible defence and retain ample potential for the future evolution of phenotypic plasticity in defence. Abstract : Larva (left) and adult (right) of the specialist herbivore diamondback moth ( Plutella xylostella ) on Eruca sativa (Brassicaceae). The results of this study suggest genetic differentiation in plasticity of defense traits between Mediterranean and desert populations of E. sativa in response to herbivory by generalist herbivores and diamondback moth in the two habitats, respectively.